Clinical significance of physical frailty in SCD subjects: A prospective study with amyloid PET data. (20th December 2022) - Lim, Eun Ye; Yang, Dong Won; CHO, Ahyun; Ho, SeongHee
Abstract: Background: Physical frailty is known to be closely associated with cognitive impairment and that it could be an early sign of Alzheimer disease (AD). We aimed to understand the characteristics of physical frailty and define factors associated with physical frailty in SCD subjects with amyloid data. Method: We prospectively enrolled SCD subjects from of cohort study to identify predictors for the clinical progression to mild cognitive impairment or dementia from subjective cognitive decline (CoSCo) study. They all went through brain magnetic resonance imaging (MRI), and Florbetaben brain amyloid‐beta Positron Emission Tomography (PET). For physical frailty, self‐reported exhaustion, hand grip strength and gait speed were measured. Result: Of total 120 SCD subjects, 26 (21.7%) subjects showed positivity in amyloid PET scan. Logistic regression analyses showed that women (OR 3.79, p = 0.002) and amyloid PET positive (OR 3.80, p = 0.008) SCD subjects showed significantly more self‐reported exhaustion. Weak hand grip strength was significantly associated with Amyloid PET positivity (OR 3.22, p = 0.047) and high burden of periventricular WMH (OR 3.34, p = 0.023). The SCD subjects with physical frailty showed lower cognitive performance in neuropsychological test, especially information‐processing speed and executive function. Conclusion: The components of physical frailty are closely related to amyloid and cerebral vascular pathology in SCD subjects and the SCD subjects with physical frailty showed lower cognitive performance in neuro‐psychological test, especially information‐processing speed and executive function.